Upaya Preventif Perilaku Menyontek Siswa Melalui Layanan Dukungan Sistem - Muhyatun, Muhyatun (Institut Agama Islam Negeri (IAIN) Curup, 2019)
The purpose of this study was to find out about the efforts made by teacher guidance and counseling at MTs. Roudlotul Banat Sidoarjo to prevent student cheating behavior. Based on the results of the teacher's guidance and counseling research at MTs. Roidlotul Bannat Sidoarjo has made several efforts that are expected to prevent students from cheating. By using system support in the form of information services and orientation guidance which is expected to provide understanding to students in cognitive, affective and psychomotor aspects regarding cheating behavior